Public work and private violence - Anders Kjelsrud; Kristin Vikan Sjurgard (University of Oslo, Department of Economics, 2020)
Violence against women is persisting in many parts of the world. At the same time, there is a global trend of increased female labour force participation. In this paper we study the effect on intimate partner violence of a large public work program in India that explicitly encourages female participation (MGNREGA). Based on detailed administrative data, we show that the work program leads to more violence against women. We argue that the effect could be explained by a "male backlash" mechanism, where husbands exercise violence to regain power within marriage.
Keywords: D19; J12; J16; 330; intimate partner violence; female employment; public work